Evidence for serpentinization of the Ionian upper mantle from simultaneous inversion of P- and S-wave arrival times. (December 2016) - D'Alessandro, Antonino; Mangano, Giorgio; D'Anna, Giuseppe; Scudero, Salvatore
Abstract: Simultaneous inversion of P- and S-wave arrival times, collected during a 3-years Ocean Bottom Seismometer with Hydrophone (OBS/H) monitoring campaign, yields 1D P- and S-wave velocity models for the Ionian lithosphere (Central Mediterranean). The 1D model highlights the presence, in the Ionian upper mantle, of two layers characterized by high seismic P-wave velocity (S1 and S2, 6.3–6.7 and 7.5 km/s, respectively). These two layers, with thicknesses of about 3.3 km and 5 km, respectively, and ranging from ∼8 to ∼16 km in depth, are characterized by low S-wave velocity (S1 = 3.05–3.2 km/s, S2 = 3.85 km/s) and high values of VP /VS (S1 = 2.06–2.09, S2 = 1.95). This is a characteristic feature, often encountered in passive margins and is generally interpreted as partly serpentinized peridotite. The VP, VS and VP /VS values of S1 are consistent with 55–65% of serpentinization of the upper mantle, while the S2 ones are consistent with 15–25% of serpentinization. This research provides a crucial hint about the debated nature of the Ionian crust, suggesting its oceanic structure.